CHANGES IN URINE MICROFLORA IN CHILDREN WITH COMMUNITY-ACQUIRED URINARY TRACT INFECTION ADMITTED TO HOSPITAL BETWEEN 1990 AND 2015: A RETROSPECTIVE FULL-DESIGN STUDY OF CASE SERIES - Olga A. Zhdanova; Tatyana L. Nastausheva; Irina V. Grebennikova; Galina A. Batishcheva; Irina Yu. Balalaeva ("Paediatrician" Publishers LLC, 2018)
Background. It is necessary to study the microbial spectrum of urine in order to determine the features of the urinary tract infection (UTI) course and to make the right choice of a therapeutic approach. Objective. Our aim was to study the structure of urine microflora in children with community-acquired UTI and its change in the period from 1990 to 2015.Methods. We conducted a continuous analysis of case histories of children admitted to hospital with UTI (pyelonephritis, cystitis, non-site specific urinary tract infection) in 1990, 2000, and 2015. We studied the results of triple (in succession) urine cultures. Shedding in a concentration of ≥ 103 cfu/ml for primary pathogens, ≥ 103 cfu/ml in boys and ≥ 104 cfu/ml in girls for secondary pathogens, ≥ 105 cfu/ml for doubtful pathogens considered to be a diagnostically significant one.Results. Members of the family Enterobacteriaceae were the main causative agents of the UTI in 1990 (found in 90.4% of 502 samples), 2000 (in 79.7% of 632 samples), and 2015 (in 67.6% of 801 samples, df = 2, p < 0.001). Escherichia coli remained the most common microorganism, the isolation rate of which decreased from 79.9% in 1990 to 39.5% in 2015 (p < 0.001). In the period from 2000 to 2015, there was a decrease in the frequency of urine detection of Enterobacter spp. (from 5.9 to 2.5%; p < 0.001) and Citrobacter spp. (from 5.2 to 1%; p < 0.001) and, on the contrary, an increase in the isolation rate of Proteus spp. (from 7.8 to 11.7%; p = 0.005), Klebsiella spp. (from 2.8 to 12.9%; p < 0.001) and Enterococcus spp. (from 1.8 to 19.1%; p < 0.001); the latter two - due to more frequent shedding in boys (by 10.5 and 19.9%, respectively).Conclusion. The Enterobacteriaceae members, mainly E. coli and Enterococcus spp., remained the predominant UTI pathogens in children in 1990, 2000, and 2015. The isolation rate of E. coli has declined significantly in recent years, whereas that of Klebsiella spp. and Enterococcus spp. has increased.